Waste Management in Sustainable Disaster Management - Ülker Aslı Güler (Doğal Afetler ve Çevre Dergisi)
Disasters cause significant damage worldwide. These damages cause an environmental and economic burden in the normalization of life, restructuring and general waste collection and disposal processes. The magnitude of a disaster is related to the concepts of existing danger and vulnerability. One of the important factors affecting the vulnerability is the concept of environment. Rapid increase in population, uncontrollable urbanization, degradation of natural environment, global climate change and unpredictable hazards and risks and affect the magnitude of disasters and create significant grievances in communities. In addition, emerged disasters can cause excess amount of debris and waste depending on their severity. A sustainable disaster management system should be implemented to reduce all these damages of disasters. In the disaster management system, waste management has an important place. Waste generated as a result of disasters, disposal options of these wastes, applied disposal methods are very important in terms of environment and public health. Disaster waste management strategies are evaluated as part of waste planning and control, waste composition and quantity, waste collection and disposal options, environmental and public health legislation. If this system is not well managed, the resulting wastes can cause significant environmental and public health problems. In this review article, the role of waste management in a sustainable disaster management is discussed based on the literature. In addition to information on disaster waste management, information was also provided on existing legislation and organizational structures.